2015
DOI: 10.1001/jama.2015.8517
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Institutional Support for Junior Biomedical Researchers

Abstract: Women are underrepresented in the biomedical research workforce. Only 30% of funded investigators are women. 1,2 Junior faculty women have fewer peer-reviewed publications than men 3,4 and are more often on clinicianeducator (vs traditional) tracks. 5 One reason may be differences in early-career institutional support, which to our knowledge has not been previously examined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
126
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 185 publications
(130 citation statements)
references
References 3 publications
1
126
0
2
Order By: Relevance
“…4 This is thought to be due to gender-related differences in negotiating salaries and startup packages, which end up potentiating over time as salaries increase by a fixed percentage. 4 Women are less likely to receive mentorship around job negotiation skills, or due to cultural norms, may be less likely to ask for higher salaries and start-up packages. 5 There also may be differences in opportunities available or in recruitment packages offered to new physician hires due to differences in perceived ability or achievement in medical school.…”
mentioning
confidence: 99%
“…4 This is thought to be due to gender-related differences in negotiating salaries and startup packages, which end up potentiating over time as salaries increase by a fixed percentage. 4 Women are less likely to receive mentorship around job negotiation skills, or due to cultural norms, may be less likely to ask for higher salaries and start-up packages. 5 There also may be differences in opportunities available or in recruitment packages offered to new physician hires due to differences in perceived ability or achievement in medical school.…”
mentioning
confidence: 99%
“…Gaps in pay or other metrics reflecting departmental investments by gender may reflect conscious or unconscious bias against women, hence examining data over time can help identify disparities and inform actions to address root causes, including gender bias [6,7]. To this end, we examined our department's performance by looking at the following domains by gender: academic rank, salary, leadership positions, and allocation of departmental resources.…”
Section: The Gender Gap In Academic Psychiatrymentioning
confidence: 99%
“…In today's society, frank discrimination, or explicit bias, is unlikely to be as important a culprit as it was in the past, although issues of salary disparity and disparities in resources afforded in research startup packages for women continue to be demonstrated. 5 However, implicit biases, the unconscious attitudes or stereotypes that affect our understanding, actions, and decisions, are pervasive. We all have them.…”
mentioning
confidence: 99%